Rapid charging provision, multiplicity and battery electric vehicle (BEV) mobility in the UK. (July 2021) - Pemberton, Simon; Nobajas, Alexandre; Waller, Richard
Abstract: This paper provides significant new insights into the spatial heterogeneity of public rapid charging provision for Battery Electric Vehicles (BEVs) in the UK. In particular, the paper makes three new and original contributions to our understanding of BEV mobility and the importance of rapid chargers and the multiplicity of rapid charging provision therein. First, the paper sets out a new conceptual framework which captures the different dimensions of BEV mobility. Second, the paper highlights the importance of multiplicity, recognising the important distinction between i) 'on-site' multiplicity; and ii) spatial multiplicity in rapid charging provision. Both have received relatively little attention to date yet are highlighted as being fundamental in shaping an individual's ability to undertake extended journeys by a BEV. Third, the paper highlights how the development of charge point multiplicity is currently largely restricted to large urban areas and strategic road networks with current policies focusing on enhancing BEV infrastructure along the TEN-T Trans-European Comprehensive Transport Network. In considering spatial multiplicity in relation to the "reserve range" of BEVs, the paper identifies spatial variations in road network connectivity. Limited interconnectivity in rural areas - and which is particularly apparent for lower range BEVs - reflects an emerging market failure with the potential to undermine efforts to secure a "just transition" to BEVs Highlights: Develops a new framework for capturing dimensions of BEV mobility. Highlights the importance of 'on-site' and 'spatial' multiplicity in BEV mobility. Identifies spatial inequities in relation to the multiplicity of BEV rapid chargers in the UK.